Neuroendocrine Transdifferentiation in Cutaneous Melanoma: A Case Report and Review of the Literature. (17th April 2023) - Pisani, David; Micallef, Daniel; Scerri, Jeanesse; Betts, Alexandra; Degaetano, James; Baldacchino, Shawn
Abstract: Neuroendocrine transdifferentiation refers to the progressive transformation of a nonneuroendocrine tumor to the one showing evidence of neuroendocrine differentiation on morphological and immunohistochemical grounds. Although this phenomenon has been well-documented in certain malignancies, particularly prostatic adenocarcinoma after androgen deprivation, cases of neuroendocrine transdifferentiation in melanomas are exceptionally rare. Herein, we report a case of a conventional superficial spreading melanoma occurring on the skin of the leg in a young male which showed progressive neuroendocrine transdifferentiation as it progressed through 2 in-transit metastases and a nodal metastatic deposit over a 4-year period. The tumor retained the BRAF V600E mutation throughout the disease process, and disease control was achieved through dual BRAF inhibition therapy. The possibility of melanoma masquerading as a high-grade neuroendocrine malignancy when investigating tumors of unknown primary should be kept in the mind of clinicians and histopathologist alike as a potential diagnostic pitfall, thus helping avoid misdiagnosis and guide appropriate treatment strategies.